New Gene Markers for Metabolic Processes and Homeostasis in Porcine Buccal Pouch Mucosa during Cells Long Term-Cultivation-A Primary Culture Approach - Dyszkiewicz-Konwińska, Marta; Nawrocki, Mariusz J; Huang, Yan; Bryja, Artur; Celichowski, Piotr; Jankowski, Maurycy; Błochowiak, Katarzyna; Mehr, Katarzyna; Bruska, Małgorzata; Nowicki, Michał; Zabel, Maciej; Kempisty, Bartosz (International journal of molecular sciences, 2018)
The oral mucosal tissue is a compound structure composed of morphologically and physiologically different cell types. The morphological modification involves genetically determined lifespan, which may be recognized as the balance between cell survival and apoptosis. Although the biochemical processes and pathways in oral mucosa, with special regards to drug transport, delivery, and metabolism, are well known, the cellular physiological homeostasis in this tissue requires further investigation. The porcine buccal pouch mucosal cells (BPMCs) collected from 20 pubertal crossbred Landrace gilts, were used in this study. Immediately after recovery, the oral mucosa was separated micro-surgically, and treated enzymatically. The dispersed cells were transferred into primary in vitro culture systems for a long-term cultivation of 30 days. After each step of in vitro culture (IVC), the cells were collected for isolation of total RNA at 24 h, 7, 15, and 30 days of IVC. While the expression was analyzed for days 7, 15, and 30, the 24th hour was used as a reference for outcome calibration. The gene expression profile was determined using Affymetrix microarray assays and necessary procedures. In results, we observed significant up-regulation of SCARB1, PTGS2, DUSP5, ITGB3, PLK2, CCL2, TGFB1, CCL8, RFC4, LYN, ETS1, REL, LIF, SPP1, and FGER1G genes, belonging to two ontological groups, namely "positive regulation of metabolic process", and "regulation of homeostatic process" at 7 day of IVC as compared to down-regulation at days 15 and 30. These findings suggest that the metabolic processes and homeostatic regulations are much more intense in porcine mucosal cells at day 7 of IVC. Moreover, the increased expression of marker genes, for both of these ontological groups, may suggest the existence of not only "morphological lifespan" during tissue keratinization, but also "physiological checkpoint" dedicated to metabolic processes in oral mucosa. This knowledge may be useful for preclinical experiments with drugs delivery and metabolism in both animals and humans.
Keywords: homeostáza; Animals; kultivované buňky; Humans; Epithelial Cells; homeostasis; Gene Expression Regulation; epitelové buňky; Swine; Cells, Cultured; regulace genové exprese; metabolic process; ústní sliznice; zvířata; prasata; Mouth Mucosa; Homeostasis; lidé; oral mucosa